Enhanced bone regeneration of the silk fibroin electrospun scaffolds through the modification of the graphene oxide functionalized by BMP-2 peptide - Wu J (Dove Medical Press, 2019)
Jiannan Wu,1,2,* Ao Zheng,1,2,* Yang Liu,3 Delong Jiao,1,2 Deliang Zeng,1,2 Xiao Wang,1,2 Lingyan Cao,1,2 Xinquan Jiang1,2 1Department of Prosthodontics, Oral Bioengineering and Regenerative Medicine Lab, Shanghai Key Laboratory of Stomatology, Ninth People’s Hospital Affiliated to Shanghai JiaoTong University, School of Medicine, Shanghai 200011, China; 2Shanghai Engineering Research Center of Advanced Dental Technology and Materials, Shanghai 200011, China; 3The State Key Laboratory of Bioreactor Engineering, East China University of Science and Technology, Shanghai 200237, China *These authors contributed equally to this work Introduction: Bone tissue engineering has become one of the most effective methods to treat bone defects. Silk fibroin (SF) is a natural protein with no physiological activities, which has features such as good biocompatibility and easy processing and causes minimal inflammatory reactions in the body. Scaffolds prepared by electrospinning SF can be used in bone tissue regeneration and repair. Graphene oxide (GO) is rich in functional groups, has good biocompatibility, and promotes osteogenic differentiation of stem cells, while bone morphogenetic protein-2 (BMP-2) polypeptide has an advantage in promoting osteogenesis induction. In this study, we attempted to graft BMP-2 polypeptide onto GO and then bonded the functionalized GO onto SF electrospun scaffolds through electrostatic interactions. The main purpose of this study was to further improve the biocompatibility of SF electrospun scaffolds, which could promote the osteogenic differentiation of bone marrow mesenchymal stem cells and the repair of bone tissue defects.Materials and methods: The successful synthesis of GO and functionalized GO was confirmed by transmission electron microscope, X-ray photoelectron spectroscopy, and thermogravimetric analysis. Scanning electron microscopy, atomic force microscopy, mechanical test, and degradation experiment confirmed the preparation of SF electrospun scaffolds and the immobilization of GO on the fibers. In vitro experiment was used to verify the biocompatibility of the composite scaffolds, and in vivo experiment was used to prove the repairing ability of the composite scaffolds for bone defects.Results: We successfully fabricated the composite scaffolds, which enhanced biocompatibility, not only promoting cell adhesion and proliferation but also greatly enhancing in vitro osteogenic differentiation of bone marrow stromal cells using either an osteogenic or non-osteogenic medium. Furthermore, transplantation of the composite scaffolds significantly promoted in vivo bone formation in critical-sized calvarial bone defects.Conclusion: These findings suggested that the incorporation of BMP-2 polypeptide-functionalized GO into chitosan-coated SF electrospun scaffolds was a viable strategy for fabricating excellent scaffolds that enhance the regeneration of bone defects. Keywords: bone morphogenetic protein-2, peptide, osteogenic differentiation, bone regeneration, graphene oxide, silk fibroin, electrospinning scaffold, bone marrow mesenchymal stem cells